Challenges and opportunities in geographical indication registered gastronomic products: Erzurum Rosette - Denk, Erkan (Frontiers in Sustainable Food Systems, 2024)
Erzurum Rosette holds significant cultural value as a traditional dessert widely produced and consumed in Erzurum. Limited knowledge exists regarding the difficulties encountered by producers and the influence of Geographical Indication (GI) registration on production and marketing. This study aims to enhance the recognition of Erzurum Rosette, assess its production process to comply with the standards of the Turkish Patent and Trademark Office (TPTO), and explore its potential as a sustainable tourist product. A qualitative analysis was conducted on six producers of Erzurum Rosette. The information was gathered through semi-structured interviews that focused on demographic data, understanding GI, production challenges, and the influence of GI registration on sales. Responses were examined using thematic coding and statistical analysis. The study revealed that this traditional dessert production involves both male and female producers and that the producers have significant professional experience. General materials for production can be easily obtained, but obtaining the necessary special iron molds poses a significant challenge. Producers with a comprehensive understanding of GI have reported increased sales and market access after registration, but those with limited understanding have seen minimal impact. Common challenges include material supply and equipment availability, particularly regarding the procurement of iron molds. Sales and marketing strategies are generally effective, but continuous innovation is necessary for market expansion. Addressing supply chain issues and increasing awareness of GI benefits for producers are crucial for the sustainability and promotion of Erzurum Rosette. Improving support for local production and targeted training initiatives can help preserve traditional production